Assessment of Vascular Endothelial Growth Factor in Fresh versus Frozen Platelet Rich Plasma. (2nd August 2015) - Hosny, Nada; Goubran, Fikry; BadrEldin Hasan, Basma; Kamel, Noha
Abstract : Platelet rich plasma (PRP) is hemoconcentration with platelets concentration above baseline values and high concentration of many growth factors. The aim of this study was to assess freezing effect on vascular endothelial growth factor (VEGF) release from PRP using two different activation methods to simplify its use in different clinical applications. PRP was prepared using two-centrifugation steps method from 12 qualified blood donors. VEGF concentrations were measured in fresh PRP and after freezing/thawing for one and three weeks with two methods of activation using (i) calcium gluconate and (ii) calcium gluconate and thrombin. Platelets count was significantly increased compared to baseline whole blood values in all fresh and frozen PRP samples ( p value was <0.05). No significant difference was found between VEGF concentrations after activating fresh and frozen-thawed PRP samples for one and three weeks by calcium alone or calcium with thrombin, and also no significant difference was found when freezing period was extended from one to three weeks. Our results showed that platelets count does not correlate with variable levels of VEGF. PRP could be prepared once and preserved frozen for at least three weeks for the next treatment sessions and activation with thrombin addition to calcium will not augment the growth factor release.